THE UTILIZATION OF BIO-FABRIC FERMENTED FROM AGRICULTURAL WASTE AS GARNITURE ON READY TO WEAR CLOTHES - Eka Oktariani; Ahmad Ibrahim Makki; Ursae Pramesvari (Balai Besar Tekstil, 2022)
Bio-fabric is a biomaterial produced by living organism, such as fungal and bacteria. The characteristic of bio-fabric is affected by constituent biomass. Bio-fabric produced by Acetobacter has a unique appearance like animal skin, hence can be utilized as animal skin material substitutes. Animal skin is a material that is still popular for fashion connoisseurs to be used as the main material and complementary material for clothing (garniture), but it has a negative impact on the environment and animal conservation. This research was carried out to obtain environmentally friendly material that has a skin-like appearance, by utilizing bacterial cellulose grown with Acetobacter bacteria. The use of different substrates as growing medium gives different bacterial cellulose characteristics, so in this study a mixture of agricultural waste (pineapple and mango pulp) was used with tea in a ratio of 1:1, 1:5, 1:10, 5:1, and 10:1 (w/w) to obtain bacterial cellulose with the best characteristics. The result of this research which presents the best yield on mango medium is at the ratio of mango: tea 1:5 with a yield of 1.35 g/g, while on pineapple medium, at the ratio of pineapple waste : tea 1:10 with a yield of 1.194 g/g. Based on the characteristic testing results, bacterial cellulose grown with pineapple waste : tea 1:10 gives the best thickness value of 0.52 mm and a tensile strength of 6890 g. This bacterial cellulose is then sewn into garniture on ready to wear clothing.